If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7(0) = -18 Multiply -7 * 0 5x + 0 = -18 Anything times zero is zero. 5x + 0 = -18 Reorder the terms: 0 + 5x = -18 Remove the zero: 5x = -18 Solving 5x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '5'. x = -3.6 Simplifying x = -3.6
| k=0 | | 5(0)-7y=-18 | | 7X+1=121-5X | | (q^2+5q+4)(q^2-1)+q^3-q=2q+2q^2-2 | | -4X+10=21+7X | | 3x-6(0)=-7 | | 3(0)-6y=-7 | | 2=-1x+45-8 | | 2=-1x+45 | | 2=-1x+9 | | 2=-1x+4 | | 3-4X=-2X+17 | | -2-8x=0 | | 4X+3=7X-12 | | -1-8x=0 | | w^2+12w+40=0 | | 4X+8=29-3X | | 4k+5=11-2k | | 7=-z+9 | | 25x^2-10x+1=0e | | 7X+2=128-7X | | 7-2(3x+2)=3x+4(x-9) | | s^2+3s-4=s^2+6s+9 | | 6-23=7x-4-6x | | 7x-6x+13=12-5 | | m=-2+5k | | 16x^2-324=0 | | -0.5x^2+176x-1440=12000 | | 4x^2-12x-72=0 | | -0.5x^2+176x-1440=0 | | 2i+8=18 | | 0.25(y+6)=2y-3(y-3) |